Peran Satuan Pendidikan Dalam Penguatan Literasi dan Numerasi Siswa Melalui Permainan Tradisional Berbasis Kearifan Lokal Sebagai Upaya Pelestarian Budaya Indonesia - Hariyani, Indaria Tri; Julianingsih, Denok; Sunarmi, Fransisca R (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2025)
Schools should be a place of learning in literacy and numeracy for students in gaining knowledge. However, it is not unlikely that schools are also less effective places for students to learn because of the weak activities of educators' abilities in literacy and numeracy in schools. The implementation of community service activities at MI Raden Rahmat Prambon Sidoarjo is based on the low reading, writing and arithmetic skills of students. Therefore, what is needed from this community service activity is to be able to accompany educational units and parents in efforts to minimize student literacy and numeracy that occurs in schools, namely the low ability to read, write and count through android-based games, and traditional games based on local wisdom as an effort to preserve Indonesian culture. With the assistance of strengthening literacy and numeracy in schools, it is also hoped that it can create an effective and efficient learning atmosphere so that learning objectives will run smoothly to create a generation of intelligent and noble nation.